Transition-Metal- and Halogen-Free Oxidation of Benzylic sp3 C–H Bonds to Carbonyl Groups Using Potassium Persulfate - Hu, Yixin; Zhou, Lihong; Lu, Wenjun (Synthesis, 2017)
Aryl carbonyl compounds including acetophenones, benzophenones, imides, and benzoic acids are prepared from benzyl substrates using potassium persulfate as oxidant with catalytic pyridine in acetonitrile under mild conditions. Neither transition metals nor halogens are involved in the reactions.
Keywords: potassium persulfate; oxidation; transition-metal-free; halogen-free; benzylic sp3 C–H bond